Prevalência de aglutininas anti-leptospira interrogans em cães de Belo Horizonte, Minas Gerais, 2001 / 02 - Danielle Ferreira de Magalhaes (2005)
The aim of this study was to evaluate the prevalence of anti-Leptospira agglutinins in dogs collected for the Zoonosis Control Center, in nine neighborhoods of Belo Horizont in different times of the year, establishing a relation between areas where dogs with positive results prevail and areas of environmental sanitation, using sources og georeference. From September 2001 to September 2002 3,417 blood samples from dogs were submitted to the microscopic agglutination test (MAT), and we found 13.11% of seropositivity, being the most reactive serovars canicola, ballum pyrogenes and icterohaemorrhagiae. Higher prevalence was found in Center southern with 22,48%, 19,12% in Eastern and 13,20 in Northeastern neughborhoods. Pampulha region, with 8,17%, presented the smallest percentage of positive reactions. The variables sex, race, age and type of apprehension reveal an increased prevalence of infection in male wandering dogs of undefined race, without difference to age. Months with highest number of dog infection were December 2001 and January 2002, corresponding to the perod of downfall and increased temperature. A closer analysis of the pattern of distribution of anti-Leptospira interrogans agglutinin shows it is widespread throughout the city of Belo Horizonte, and there are areas with different risk level. Those with higher risk are villages, slums and suburbs with environmental sanitation deficiency.